Strategi TaRL sebagai Upaya Peningkatan Keaktifan dan Hasil Belajar dalam Mata Pelajaran Matematika Di Kelas III Sekolah Dasar - Hardiyanto, Tommy; Heryanto, Toni; Asyiah, Nur; Khotimah, Firliani (Mataram University, 2025)
Education at the elementary school level plays a crucial role in building the foundation of knowledge and essential skills for individuals. One of the subjects that holds a fundamental role in developing logical and systematic thinking is mathematics. A solid understanding of mathematical concepts is essential for students to optimally develop their academic abilities and cognitive skills. This study employed a Classroom Action Research design by implementing the Teaching at the Right Level (TaRL) learning approach, which aims to examine students’ activeness and understanding in the mathematics topic of data collection and presentation. The results indicated a significant improvement in both students’ engagement and learning outcomes. Based on observational data, students’ activeness increased from 34.97 in the pre-cycle to 58.33 in the first cycle, and eventually reached 82.14 in the second cycle. This illustrates that students became more actively involved in the learning process as instruction became more aligned with their individual needs. A similar pattern was observed in students’ learning test scores, which increased from 50.71 in the pre-cycle to 64.64 in the first cycle, and further improved to 80.35 in the second cycle. The study concludes that the gradual implementation of the Teaching at the Right Level (TaRL) approach significantly enhances both student engagement and learning outcomes, as evidenced by the overall research findings.